PERSEPSI ORANG TUA PAUD DALAM MEMPERSIAPKAN ANAK MEMASUKI JENJANG PENDIDIKAN DASAR - Nur, Maulida; Anggraeni, Ira; Risna, Inten (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
The PAUD to Elementary School Transition Movement is a movement released by the Ministry of Research, Technology and Culture.  This transition movement is expected to be not just a breath of fresh air as a mere policy. But it can be realized according to the government's goal of creating a pleasant transition for PAUD children to enter the elementary level.  Of course, this needs various parties to work together to make it happen, starting from the exit, teachers, schools and policy makers. The period of early childhood education to the level of elementary education can be called the transition period from early childhood education to elementary school. The transition from PAUD to elementary school is a critical stage for children. During the transition period, children are usually not ready to receive the learning process in elementary school. If the transition stage fails, the next learning process will also fail. The transition from PAUD to elementary school must certainly have readiness for children, parental readiness and school readiness. Parents are in the scope of the family and the family is the closest educational scope of a child, parents are a crucial role in the readiness of children to go to school. Parents' perception of how their children are ready is certainly different. This is a preliminary study by the researcher with the aim of having a basis for further research on the transition from early childhood education to elementary school. The research method used is descriptive qualitative research, with interview techniques, from this research there are three themes, namely the perception of children's readiness to enter the elementary level, the perception of parents' preparation to enter the early childhood level and the dilemma of parents in preparing their children to enter the elementary education level